The effect of the IRE strategy using lasers on some functional and physical variables in student football - جاسم, م.د ضياء رحمن; Saham, Asst.L. Mustafa Zuhair; موسى, ا . م . د حيدر جابر (Sulaimani Journal for Humanities, 2026)
The research aimed to identify the effect of the IRE strategy using laser beams on some functional and physical variables in football for students. The research problem lies in the weakness of the students' physical and skill performance. The research hypothesis is that there is an effect of the IRE strategy using laser beams on some functional and physical variables in football for students. The researchers used the experimental method as it is suitable for the research problem. The research sample consisted of first-year students from the University of Kufa, numbering (24) students, and they were divided into two groups, experimental and control, with each group consisting of (12) students. Several means and tools were used to collect data, including questionnaires and sources. Then the researchers used the statistical package (SPSS). The researchers concluded that the IRE strategy using laser beams has a positive effect on some functional and physical variables in football for the students under study. The conclusions also showed that there is an improvement in the functional variables in which the laser was used through the zigzag running and long jump tests. The most important recommendation was to emphasize the use of the IRE strategy using laser beams on some functional and physical variables in football for students.
Keywords: IRE Strategy; Functional Physical; Lasers for; Football